The principle of legal certainty in european and national law (meaningful response) - Богачова, Л. Л. (Theory and practice of jurisprudence, 2016)
A comparative legal analysis of the concept and content of the principle of legal certainty, examined the features and the scope of its use in the practice of the European Court of Human Rights and the Constitutional Court of Ukraine.